Mecanismo de Desenvolvimento Limpo e eficácia das medidas de compensação de reduções certificadas de emissões: análise de projetos aplicados à mineração - Molino, Fernanda Brusa (2013)
Industrialization, that was already seen as synonymous of progress and hope of a better future for most nations, reaches the XXIth century facing many detractors and being seen as a major threat because of its voracious consumption of raw material which exhausts seas, forests, soil, subsoil and releases harmful gases that contribute to the greenhouse effect, causing the reaction of sectors of society concerned with the legacy that will be let to future generations. Among most harming sectors, are mining and related industry, whose degrading and polluting activities demonstrates the need for quality control and environmental monitoring. This study seeks to contextualize the concern about global warming and the rise of international treaties on the subject for the defense of the environment, mentioning Kyoto Protocol, Intergovernmental Negotiating Committee for a Framework Convention on Climate Change (INC/FCCC), the conferences between the parties, and also the Brazilian legislation related to the issue of climate change mitigation. The study seeks to know about the flexibility mechanisms proposed by Kyoto Protocol, aiming to achieve emission reductions by developed countries signatories. The research analyzes the Clean Development Mechanism (CDM), the Certified Emission Reductions (CER) and the efficiency of these instruments as a form of environmental compensation, highlighting the various modalities, to finish with the presentation of the carbon market and CDM related projects that help in global warming mitigation undertaken by mining sector. Among the findings, it appears that compensation measures are able to meet the recommendations of the Kyoto Protocol and to assist in combating the adverse effects of mining to the environment